Efficacy of tranexamic acid in reducing blood loss during lower segment caesarean section - Gobbur, Vijayalaxmi Raghavendra; Shiragur, Shobha Shivanand; Jhanwar, Usha R.; Tehalia, Manpreetkaur Jaspal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of current study was to study the efficacy of tranexamic acid in reducing blood loss during and after lower segment caesarean section. Methods: A randomized, case controlled, prospective study was conducted on 100 women undergoing lower segment caesarean section (LSCS between Oct 2007 and Oct 2009). Fifty of them were given tranexamic acid 1 gm slow IV 20 minutes before LSCS & were compared with 50 others to whom tranexamic acid was not given. Blood loss was collected and measured during two periods. The first period was from placental delivery to end of LSCS and second from the end of LSCS to 2 hours postpartum. Results: Tranexamic acid significantly reduced the quantity of blood loss during LSCS 289.4 ± 71.4 ml in the study group versus 328 ± 58.9 ml in the control group (P = 0.004). It also significantly reduced the quantity of blood loss from placental delivery to 2 hours post-partum: 360.9 ± 110.3 ml in the study group, versus 443 ± 88.55 ml in the control group. (P = 0.0008). No complications or side effects were reported in either group. Conclusions: Tranexamic acid significantly reduces the blood loss during and after the caesarean section. Side effects like nausea, vomiting, diarrhoea & thrombosis are rare. Tranexamic acid can be used effectively in women undergoing LSCS to decrease the blood loss.